Hydrogen isotopic substitution experiments in nanostructured porous silicon - Palacios, W. D. (2008)
Nanostructured porous silicon is usually prepared by electrochemical anodization of monocrystalline silicon using a fluorine-rich electrolyte. As a result of this process, the silicon atoms conserve their original crystalline location, and many of the dangling bonds appearing on the surface of the nanostructure are saturated by hydrogen coming from the electrolyte. This work presents an IR study of the effects produced by partial substitution of water in the electrolytic solution by deuterium oxide. The isotopic effects on the IR spectra are analyzed for the as-prepared samples and for the samples subjected to partial thermal effusion of hydrogen and deuterium. We demonstrate that, although deuterium is chemically indistinguishable from hydrogen, it presents a singular behaviour when used in porous silicon preparation. We found that deuterium preferentially bonds forming SiDH groups. A possible explanation of the phenomenon is presented, based on the different diffusivities of hydrogen and deuterium.